2021
DOI: 10.1055/a-1207-0557
|View full text |Cite
|
Sign up to set email alerts
|

Does Nutrition Affect Endometriosis?

Abstract: Endometriosis is a hormone-related, chronic inflammation in women of childbearing age. The aetiology and pathogenesis of endometriosis are not yet fully understood. For other illnesses classed as lifestyle diseases, the link between nutrition and pathogenesis has already been researched and proven. With regard to these findings, the question continues to arise as to whether and how a specific diet and lifestyle could also influence pathogenesis and the progression of endometriosis. The aim of this review is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
0
20
0
5
Order By: Relevance
“…Excess caffeine and any amount of alcohol usually cause a flare, so I mostly avoid these. Recent literature has shown that both caffeine and alcohol increase the bioavailability of estrogen, which is detrimental for an estrogen-dependent disease [15]. Over the years, I have learned to identify a cyst rupture.…”
Section: Managing Symptomsmentioning
confidence: 99%
“…Excess caffeine and any amount of alcohol usually cause a flare, so I mostly avoid these. Recent literature has shown that both caffeine and alcohol increase the bioavailability of estrogen, which is detrimental for an estrogen-dependent disease [15]. Over the years, I have learned to identify a cyst rupture.…”
Section: Managing Symptomsmentioning
confidence: 99%
“…Additionally, Helbig et al, (2021) performed a literature search for articles from 2000 onwards to answer the question whether diet influences the risk for and progression of endometriosis or whether it influences the postoperative condition [54]. This review did not take the effect of diet on pain symptoms into account.…”
Section: Nirgianakis Et Al (2021) Performed a Systematic Review On The Effectiveness Of Dietary Interventions In The Treatment Of Endometmentioning
confidence: 99%
“…Endometriosis is a hormone-dependent gynecologic disorder defined as the presence of endometrial-like tissue outside the uterine cavity. It is a chronic inflammatory disease that may be progressive in many cases 1,2 . Endometriosis predominantly affects women of reproductive age (10%) 3 .…”
Section: Introductionmentioning
confidence: 99%